2020
DOI: 10.56093/ijas.v90i5.104357
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and divergence studies in mungbean (Vigna radiata) under rainfed conditions

Abstract: Twenty three genotypes of moongbean were evaluated in two different environments for variability stability performance. The present investigation was conducted to provide information on the nature and magnitude of genetic variability and divergence among 23 genotypes of mungbean under different environments. It was measured by seed yield/plant under rainfed conditions during kharif 2016 and 2017. Seed yield/plant showed significant correlation with number of seeds/pod and negative correlation with days to matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Mean value of seed yield/plant revealed that genotype PU-15-2 acquired maximum contribution (8.27 g) while NU-1 was found extremely poor with the lowest contribution (4.12 g). Similar outcomes have been published by Kumar et al (2020) for days to 50% flowering (DTF), plant height (PH), number of branches/plant (NOBP), pod length (PL), number of seeds/pod (NSPP), and seed yield/plant (SYPP).…”
supporting
confidence: 73%
See 3 more Smart Citations
“…Mean value of seed yield/plant revealed that genotype PU-15-2 acquired maximum contribution (8.27 g) while NU-1 was found extremely poor with the lowest contribution (4.12 g). Similar outcomes have been published by Kumar et al (2020) for days to 50% flowering (DTF), plant height (PH), number of branches/plant (NOBP), pod length (PL), number of seeds/pod (NSPP), and seed yield/plant (SYPP).…”
supporting
confidence: 73%
“…Ten out of the 30 genotypes demonstrated below-average performance suggesting an early flowering in blackgram. Kumar et al (2020) published similar results with respect to days to 50% flowering. Genotype PU-13-05 exhibited the highest number of branches/plant (8.53), while PU-15-26 least (4.17).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…MSG= Mean squares of genotypes; MSE = Mean squares of error; r = Number of replications. Phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) was estimated according to Burton, (1952) and Kumar et al, (1985) Broad sense heritability (h 2 b ) was evaluated following the methods described by Acquaah (2017) as follows:…”
mentioning
confidence: 99%